The effect of scoring correction and model fit on the estimation of ability parameter and person fit on polytomous item response theory - Santoso, Agus; Pardede, Timbul; Djidu, Hasan; Apino, Ezi; Rafi, Ibnu; Rosyada, Munaya Nikma; Abd Hamid, Harris Shah (Graduate School of Universitas Negeri Yogyakarta & Himpunan Evaluasi Pendidikan Indonesia (HEPI), 2022)
Scoring quality has been recognized as one of the important aspects that should be of concern to both test developers and users. This study aimed to investigate the effect of scoring correction and model fit on the estimation of ability parameters and person fit in the polytomous item response theory. The result of 165 students in the Statistics course (SATS4410) test at one of the universities in Indonesia was used to answer the problems in this study. The polytomous data obtained from scoring the test results were analyzed using the Item Response Theory (IRT) approach with the Partial Credit Model (PCM), Graded Response Model (GRM), and Generalized Partial Credit Model (GPCM). The effect of scoring correction and model fit on the estimation of ability and person fit was tested using multivariate analysis. Among the three models used, GRM showed the best fit based on p-value and RSMEA. The results of the analysis also showed that there was no significant effect of scoring correction and model fit on the estimation of the test taker's ability and person fit. From the results of this study, we recommend the importance of evaluating the levels or categories used in scoring student work on a test.